THE POSSIBILITY OF FORMING AN EFFECTIVE MECHANISM ATTRACTING FOREIGN INVESTMENTS IN THE ELECTRIC POWER INDUSTRY OF THE RUSSIAN FEDERATION: STRESS TESTING AND REAL OPTIONS METHOD - Y. Zubkova (Вестник университета)
The article considers a challenging issue of creating an effective mechanism for attracting foreign investments in the Russian electric power industry. Based on the findings about the shortcomings of the existing mechanisms the author identified the basic requirements that must be met by a new investment mechanism. It proves the importance of phased and multi-scenario planning long-term development strategy of the industry, including stress modeling in assessing the sustainability of projects and the sector as a whole. Using the proposed method of real options in a new investment mechanism can reduce the negative impact from the implementation of shock risks and to provide a systematic approach to the regulation of the industry, which will increase its attractiveness for foreign investors.